Towards sustainability : the European Commission's progress report and action plan on the fifth programme of policy and action in relation to the environment and sustainable development. (Office for Official Publications of the European Communities, 1997)
The report seeks to identify the influence of the programme on the environment and on progress towards sustainable development in the light of events and trends which have emerged since the programme was adopted.